First Observations of G‐Band Radar Doppler Spectra. Issue 4 (17th February 2022) - Courtier, Benjamin M.; Battaglia, Alessandro; Huggard, Peter G.; Westbrook, Chris; Mroz, Kamil; Dhillon, Ranvir S.; Walden, Christopher J.; Howells, Gareth; Wang, Hui; Ellison, Brian N.; Reeves, Richard; Robertson, Duncan A.; et al.
Abstract: The first Doppler spectra ever acquired by an atmospheric radar at 200 GHz (G‐band) are presented. The observations were taken during a light precipitation event in May (rain rates <2 mm hr −1 ) at Chilbolton Observatory, UK, with coincident Ka‐band and W‐band Doppler radar measurements. The collected rain spectra agree with Mie theory predictions: at G‐band they show significant reductions in the spectral power return—as compared to theoretical Rayleigh scattering—corresponding to high Doppler velocities (i.e., large raindrops) with the presence of multiple peaks and "Mie notches" in correspondence to the maxima and minima of the raindrop backscattering cross sections. The first two G‐band Mie troughs correspond to smaller velocities/sizes than the first W‐band Mie notch. These features offered by G‐band radars pave the way toward applying, in rain, Mie notch vertical wind retrievals and multifrequency drop size distribution microphysical retrievals to smaller rain rates and smaller characteristic sizes than ever before. Plain Language Summary: The first Doppler velocity measurements ever acquired by an atmospheric radar at 200 GHz (in the so‐called G‐band) are presented. The observations were taken during a light precipitation event in May (rain rates <2 mm hr −1 ) at the STFC Chilbolton Observatory, UK, with coincident measurements at 35 and 94 GHz. At high Doppler velocities (i.e., in correspondence to large raindrops) the collected G‐band Doppler velocity spectra show significant non‐Rayleigh effects, as expected from scattering Mie theory when the wavelength is much larger than the scattering target dimension. This is highlighted by the presence of multiple peaks and minima in the spectral power return and by a significant reduction of the spectral power at G‐band compared to the other frequencies. The first two G‐band minima both correspond to smaller velocities/sizes than the first W‐band minimum, a direct consequence of the reduced wavelength of the G‐band radar. These novel features observed by G‐band radars pave the way toward applying, in rain, vertical wind retrievals and multifrequency drop size distribution retrievals to smaller rain rates and smaller characteristic drop sizes than ever before. Key Points: The first Doppler spectra ever acquired by an atmospheric radar at 200 GHz (G‐band) are presented The G‐band spectra in rain show the presence of Mie notches, as expected from Mie scattering theory The G‐band spectra pave the way toward applying vertical wind and multifrequency DSD retrievals at smaller rain rates than ever before